Qualidade de melancias durante o desenvolvimento em diferentes doses de fósforo - Paiva, Cristiane Alves de (2017)
The fruit quality characteristics are altered by the cultivar, maturity stage, environmental conditions and crop management. In general, the availability of nutrients for the plants affect the growth, yield and fruit quality. Thus, this work aimed to evaluate the quality of watermelon with seeds 'Magnum' and seedless 'Style' at different stages of development grown under different phosphorus levels. The experiment was established in the municipality of Mossoró-RN, in experimental design of randomized blocks, with 24 treatments, two phosphorus levels (30 and 130 kg / ha), applied to the foundation, at a dose of 0 kg P/ha, without development of plants and/or fruits; with two watermelon cultivars (Magnum and Style) and six stages of development, conferred after anthesis (AA). For this, the female flowers were marked with different colored ribbons, starting the fruit harvest in the effective training, 12 days after anthesis (DAA), and interval of six days to 42 DAA. The following quality characteristics were evaluated in the fruit flesh firmness (PF), flesh color (L, a * and b *), glucose, fructose, sucrose, soluble solids (SS), starch, titratable acidity (TA), relationship SS/TA, ascorbic acid (AA) and lycopene. The treatments were subjected to analysis of variance; qualitative variables were compared by Tukey test at 5% probability, and the quantitative regression. In cultivation at 30 kg/ha P2O5, watermelon FP was higher. The cv. 'Magnum' showed higher fresh weight during development. The coloration a * and b * increased and the lightness (L *) of the pulp decreased with the development of fruit. The 'Magnum' watermelon accumulated higher SS; and 30 DAA SS content (11%) was higher than the watermelon 'Style' (9.8%). Fructose increased to 30 DAA to cv. 'Style' and 24 DAA for cv. 'Magnum'. Glucose increased to 24.77 DAA for both cultivars, but the sucrose content of the watermelon 'Magnum' was higher at 42 DAA. The starch content increased to 36 DAA, but watermelon 'Style' and remained higher content, the dose of P did not alter this attribute, but in watermelon "Magnum" the cultivation higher dose of P increased starch content. The SS / TA ratio of fruit was higher for watermelon 'Magnum' 42 DAA. Cultivation with the dose of 30 kg increased the SS/TA ratio of fruit in commercial maturity. AT fruit decreased from 21,15 DAA and the growing dose of 130 kg/ha P2O5 provided greater AT fruits. The highest lycopene accumulation occurred in the fruit until 38.65 DAA and was higher in watermelon 'Style'. Ascorbic acid increased by 30 DAA in watermelon 'Magnum' cultivated with 30 and 130 kg P2O5 and in watermelon 'Style' varied independently P doses. In both cultivars, there is a decline in ascorbic acid content from 36 DAA